Isolation and characterization of antihypertensive peptides from soy bean protein (Brazilian Journal of Pharmaceutical Sciences, 2022)
Proteins and peptides are the most diverse biomolecules found in nature and make our interest due to their wide applications in food and pharmaceutical industry. Angiotensin Converting Enzyme (ACE) plays a major role in controlling blood pressure. The inhibition of ACE with peptides is a main target in the regulation of hypertension. The objective of the present study was to investigate the therapeutic potential of soy bean. This was accomplished by isolation of ACE inhibitory peptides using response surface methodology (RSM) and characterization of these bioactive peptides by mass spectrometry. 31 hydrolyzed fractions were isolated and evaluated for their ACE inhibition potential. Hydrolyzed fraction having highest ACE inhibitory activity was characterized by liquid chromatography-mass spectrometry (LC-MS) technique. RSM results showed maximum ACE inhibition potential (64%) by hydrolyzate was obtained at 45 ºC temperature, pH 8.0, E/S 0.2 in 2 hours hydrolysis time. Results of LC-MS analysis revealed Ser-Gly, Ser-Pro, Met-Ala, His-Ala, Lys-Pro, Phe-Thr, Met-Leu, Pro-Arg, Ala-Pro-Val, Pro-Ala-Leu, Val-Met-Gly, Pro-Leu-Val, Pro-Pro-Gln, His-Arg-Gly, Ser-Phe-Val-Leu, Ala-Val-His-Try, Arg-Thr-Val-Arg, His-His-Tyr-Leu-Val, Asp-Gly-Ala-Cys-Ser-Ala-Asn and MetVal-Thr-Gly-Pro-Gly-Cys-His bioactive peptides in hydrolyzed fraction of soy bean. Our data provide evidence that response surface methodology is a good approach for isolation of antihypertensive bioactive peptides with more potent activity as nutraceuticals or pharmaceuticals. Therefore soy bean can be use for industrial production of pharmaceutical grade natural medicines for handling high blood pressure.